A validated micellar LC method for simultaneous determination of furosemide, metoprolol and verapamil in human plasma. (January 2012) - Soltani, Somaieh; Jouyban, Abolghasem
An accurate and precise micellar LC method coupled with UV and fluorimetric detectors was developed and validated for the simultaneous analysis of furosemide, metoprolol and verapamil in human plasma. The total analysis time was 25 min (12 min for sample preparation and 13 min for drug separation). All drugs possessed linear behavior (r > 0.999 for calibration curves) in their therapeutic concentrations. The mean drug recoveries were 101.9, 100.1 and 100.2% for furosemide, metoprolol and verapamil, respectively. The accuracies (relative error %) were less than 15% for all drugs. Intra- and inter-day precisions (RSD%) were less than 15% and the stability data were acceptable according to the US FDA guideline for bioanalytical method validation.